Learning Hadoop 2 : design and implement data processing, lifecycle management, and analytic workflows with the cutting-edge toolbox of Hadoop 2 /: design and implement data processing, lifecycle management, and analytic workflows with the cutting-edge toolbox of Hadoop 2. (2015) - Turkington, Garry; Modena, Gabriele
No abstract available